Lettuce Yield (Lactuca sativa L.) Under Different Irrigation Regimes and Nitrogen Dose in the Imperial Valley, California - Buenrostro-Curiel, Juan; Montazar, Aliasghar; Avilés-Marín, Silvia Mónica; Escobosa-García, María Isabel; Brígido-Morales, Juan Gabriel; Soto-Ortiz, Roberto (REVISTA TERRA LATINOAMERICANA, 2025)
Lettuce is one of the most widely consumed vegetables globally. China is the leading producer of this crop, followed by the United States, which produces 3.3 million tons per year, with 90% of production concentrated in the south-western region, primarily in the states of California and Arizona. Various studies indicate that nitrogen fertilizer application rates between 363 and 470 kg ha-¹ achieve the highest yields in loose-leaf and ‘iceberg’ lettuce cultivation. However, of this application rate, only 40% of the nitrogen is absorbed by the crop, while the remainder is lost through leaching processes. This issue is compounded by the indiscriminate use of irrigation rates, which vary according to climatic conditions, ranging from 0.45 m ha-¹ in Colombia to 2.0 m ha-¹ in California. These two factors contribute to groundwater contamination and increase production costs. The objective of this study was to evaluate, in terms of yield, two different irrigation rates and three nitrogen fertilization levels using a split-plot design arranged in a randomized complete block with four replicates. The variables analysed included NDVI index, chlorophyll content, stomatal conductance, sap nitrate concentration, yield, and dry biomass weight of lettuce. The results show no statistically significant differences in yield based on the different irrigation rates and nitrogen fertilization levels, suggesting that a change in the current technological package for this crop is feasible, allowing for the application of the treatment with the lowest irrigation rate (0.62 m ha-¹) and lower fertilization (94 kg ha-¹).